Spatial modelling of acute respitory infection with environmental health factors in Gowa Regency, Indonesia - Hadriani Hadriani; Andi Susilawaty; Emmi Bujawati (Al-Sihah : The Public Health Science Journal, 2020)
Respiratory tract infections or ISPA is an infection that occurs in the nasal cavity, sinuses, and throat. ISPA is caused by influenza viruses, parainfluenza, and other typical viruses. The purpose of this study is to determine the spatial description of the environmental factor on ISPA disease in the working area of Gowa Regency, Indonesia. This research employs a quantitative research methodology by using a descriptive approach. The method used in this research was a spatial pattern. The research results showed that the spread of ISPA disease could be restrained based on several measurements. It reveals that the ventilation area of the respondent's house was 66.3% in which it did not meet the proper ventilation standards; the type of the wall used in the respondent's house was 25.0% which did not meet the proper wall standard; the type of floor used in the respondent's house was 31.3% which did not meet the proper floor standard; the density of the respondent’s house was 31.3% in which the occupancy density did not meet the proper density standard; the room temperature of the respondent’s house was 27.5% which did not meet the proper temperature standard, and lastly the spread of ISPA disease based on the humidity of the respondent's room was 32.5% which means that the room humidity did not meet the proper humidity standard. Based on the research results, it is expected that a clear understanding of the importance of maintaining a clean home environment could be gained.